The girl with the shark's teeth - Burnell, Cerrie (Oxford, England, UK : Oxford University Press, 2018)
Minnow is different from the other girls in her town and there's plenty to set her apart: the blossom of pale scars which lie beneath Minnow's delicate ears, the fact that she has an affinity with the water which leaves people speechless and that once she is sure, in deep, deep water, her body began to glow like a sunken star. When her mum gets into trouble and is taken from their boat in the dead of night, Minnow is alone with one instruction: sail to Reykjavik to find your grandmother, she will keep you safe. Minnow has never sailed on her own before, but the call of the deep is a call she's been waiting to answer her whole young life. Perhaps a girl who is lost on land can be found in the Wild Deep.
GS
Text in English
Keywords: Girls -- Juvenile fiction; Sailing -- Juvenile fiction; Fantasy fiction; Children's stories